Navigating Constitutional Constraints: State Governance Practices of The Indonesian President - Rahmat Syahid Suraya; Dmitry Ivanovich Pobedash (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The focus of this study is to examine the substance of the president's authority restrictions in establishing constitutional governance in Indonesia. The president's limitation of power is connected to the president's restriction of authority. On the other hand, the president's power can be limited by the functional relationship between the president and the House of Representative Council (DPR), the Representative People Assembly (MPR), the Local Representative Council (DPD), and the Supreme Court (MA) and the Constitutional Court (MK). The study's findings indicate that the restricted content of the president's power can be viewed not only in terms of the president's time in office but also in terms of the content president's authority, i.e. restrictions on choosing state officers and restrictions on law-making and that the restricted content president power can be viewed in terms of the president's functional relationship with legislative and constitutive institutions.